2018
DOI: 10.1007/s00234-018-2062-9
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin-labeling perfusion imaging of childhood encephalitis: correlation with seizure and clinical outcome

Abstract: In childhood encephalitis, patients with extreme global hypoperfusion had poor neurological outcome and those with focal hypoperfusion were more likely to have seizure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Only one patient who manifested recurrent convulsive seizures followed by fever and headache was treated only with intravenous acyclovir, but she did not suffer from relapse for 2 years, hence, MOG antibody-positive UCCE may represent corticosteroid-responsive encephalitis and benign phenotype, but there is no agreement on the dose of the hormone. In addition, study indicated that MOG-Ab dynamics and their faster negativity would be an implication for good prognosis [14] , besides a research from childhood encephalitis showed that cases with brain hypoperfusion had poor neurological outcome and those with local hypertransfusion were more likely to have seizure [15] , which imply that cerebral perfusion may be associated with prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…Only one patient who manifested recurrent convulsive seizures followed by fever and headache was treated only with intravenous acyclovir, but she did not suffer from relapse for 2 years, hence, MOG antibody-positive UCCE may represent corticosteroid-responsive encephalitis and benign phenotype, but there is no agreement on the dose of the hormone. In addition, study indicated that MOG-Ab dynamics and their faster negativity would be an implication for good prognosis [14] , besides a research from childhood encephalitis showed that cases with brain hypoperfusion had poor neurological outcome and those with local hypertransfusion were more likely to have seizure [15] , which imply that cerebral perfusion may be associated with prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…Other physiologic neuroimaging techniques, such as perfusion imaging, may reflect more recent physiologic changes in the brain during the early stage of encephalitis. 15 Future studies might employ perfusion MRI to assess the cerebral blood flow of patients with rhombencephalitis and correlate these changes with the consciousness of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome was graded by using the Glasgow Outcome Scale (GOS) at the end of the first week and 12th month after the onset of disease: 1, death; 2, neurovegetative state; 3, severe disability incompatible with independent living; 4, moderate disability but compatible with independence; and 5, full recovery. 12,14,15…”
Section: Mri Analysismentioning
confidence: 99%
“…However, in mild encephalopathy with a reversible splenial lesion (MERS), the T2-hyperintensity and restricted diffusion of the splenial leison resolve completely or near completely on follow-up imaging within days to weeks and affected children usually have good outcomes [ 81 ]. Perfusion imaging (ASL imaging) may show elevated cerebral blood flow, suggestive of seizure activity [ 82 ]. In addition, diffuse hypoperfusion of the brain indicates poor clinical outcomes.…”
Section: Mr Neuroimagingmentioning
confidence: 99%